PENERIMAAN DIRI PADA LANJUT USIA DITINJAU DARI KEMATANGAN EMOSI - Endah Puspita Sari; Sartini Nuryoto (Faculty of Psychology, Universitas Gadjah Mada, 2002)
The goal of this research is to know the correlation between emotional maturity and self-acceptance of the old people. The dependence variable of this research is self-acceptance, which is measured by self-acceptance scale. The independence variable is emotional maturity, which is measured by emotional maturity scale. This research is applied to the 32 old people, the minimal age is 65, retired, can still response to the items, and does not live in the Panti Sosial Tresna Werdha. The quantitative analysis, the correlation analysis of the emotional maturity score and self-acceptance score, show that there is a positive correlation between emotional maturity and self-acceptance of the old people. Keywords: emotional maturity, self-acceptance, old people